A rare case report of total uterine rupture from cervix to fundus in an unmarried teenage pregnancy - Elango, Shanthi K.; Taj, Rizwana; Mohan, Monisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Uterine rupture is an uncommon and a life threatening obstetric complication. It is mainly a result of delivery by untrained personnel. This is a catastrophic situation where there is a high mortality rate for both the mother and the baby and a nightmare for the obstetrician also. There are many cases of uterine trauma reported in which there may be scar dehiscence, scar rupture, uterine rupture,perforation, cervical injuries, colporrhexis etc.This case report is regarding an unusual and rare presentation of a 19 year old unmarried girl who landed in our institution-a case of total and complete uterine rupture extending from cervix to fundus, a peculiar presentation, a hazardous result of Youtube delivery by her boyfriend highlighted. A scenario where the maternal anatomy totally distorted due to the trauma. This patient managed by immediate resuscitation and uterus reconstructive surgery successfully. In spite of the advice not to conceive for the next few years, patient turned back to us in the late trimester within the next year itself, again a big challenge. Both the mother and baby managed successfully .With this case report we emphasize the need for immediate intervention in case of suspected uterine rupture and the possibility of successful subsequent pregnancy highlighted.